Selenium levels in hospitalized preterm very low birth weight neonates in North India - Gupta, Arohi; Kumar, Mala; Tripathi, Shalini; Singh, Kalpana; Singh, V. K.; Anand, Tarun (Indian Journal of Child Health, 2019)
Background: Most of the morbidity and mortality of very low birth weight (VLBW) neonates are due to oxidative stress and infection. Selenium can address these issues due to its antioxidant role and synthesis of glutathione peroxidase for scavenging free radicals. Objective: The objective of the study was to find the serum selenium levels in hospitalized preterm VLBW neonates. Materials and Methods: This was a prospective observational study conducted in the Neonatal Unit of Department of Paediatrics in a tertiary care hospital, Lucknow, for the duration of 1 year. A total of 126 preterm VLBW neonates admitted within 72 h of birth and having a venepuncture for any reason were enrolled, and those with major congenital abnormality, prior supplementation, and necrotizing enterocolitis on admission were excluded. Blood sample was collected after enrollment in plain vacutainer under aseptic precautions and after ½ h serum was separated by centrifugation. Selenium levels were estimated in serum by inductively coupled plasma optical emission spectrometry method (Perkin Elmer Optima 8000). Results: Mean birth weight was 1150±210 g and mean gestational age was 30.21±3.76 weeks in our study population. Mean levels of selenium were 9.49±3.49 ?g/dl. Mean selenium levels in neonates with gestational age <30 weeks, 30–32, and >32 weeks were 8.90±3.32, 9.32±3.74, and 10.57±3.15 ?g/dl (p=0.107), respectively. Thus, the selenium levels were seen increasing with an increase in the gestational age. Furthermore, serum selenium level of neonates with birth weight >1 kg (10.08±3.55 ?g/dl) was found to be significantly higher than those with birth weight ?1 kg (8.40±3.12 ?g/dl) (p=0.009). No significant association was seen with birth centiles or gender. Conclusion: Serum selenium levels were significantly lower in preterm neonates with lesser gestational age and lower birth weight although the baseline levels were within normal limits. Thus, the significant difference in levels can be linked with most of the morbidities and mortality in preterm neonates.